Micro-manufacturing technologies and their applications : a theoretical and practical guide - Fassi, Irene; Shipley, David (Springer, 2017)
This book provides in-depth theoretical and practical information on recent advances in micro-manufacturing technologies and processes, covering such topics as micro-injection moulding, micro-cutting, micro-EDM, micro-assembly, micro-additive manufacturing, moulded interconnected devices, and microscale metrology. It is designed to provide complementary material for the related e-learning platform on micro-manufacturing developed within the framework of the Leonardo da Vinci project 2013-3748/542424: MIMAN-T: Micro-Manufacturing Training System for SMEs. The book is mainly addressed to technicians and prospective professionals in the sector and will serve as an easily usable tool to facilitate the translation of micro-manufacturing technologies into tangible industrial benefits. Numerous examples are included to assist readers in learning and implementing the described technologies. In addition, an individual chapter is devoted to technological foresight, addressing market analysis and business models for micro-manufacturers.
Includes index.
Keywords: Microfabrication.; elektronické knihy; electronic books